Biotechnology for Conservation and Utilization of Agricultural Plant Genetic Resources in Nepal - Joshi, Bal Krishna (Journal of Nepal Agricultural Research Council, 2017)
Agricultural biodiversity is the basis of human life and food security. Nepal with 577 cultivated species possesses huge diversity at varietal as well as landrace levels. In most agricultural crops the rapid genetic erosion due to several reasons is a common phenomenon. Thus, considering the importance of agricultural biodiversity declared by Convention on Biological Diversity for sustainable food production, National Agriculture Genetic Resources Center (NAGRC) has been established for conservation and sustainable utilization of agricultural biodiversity. This paper thus delineates the application of biotechnological tools adopted by NAGRC for effective and efficient conservation and use of agricultural plant genetic resources (APGRs). Among the adopted technologies, tissue bank using shoot tip culture of vegetatively propagating and recalcitrant crops eg potato, sugarcane, banana, sweet potato, etc are in function. Under the molecular marker technology, currently random amplified polymorphic DNA (RAPD) and simple sequence repeat (SSR) markers have been used for developing DNA profiles, identifying duplicates in the collections, assessing genetic diversity and screening accessions against economic traits. DNA bank has also been created for storing DNA of indigenous crops and these DNA can be accessed for research and study. Genotypic database has been developed for chayote, finger millet, wheat and maize for identification and selection of the accessions. Journal of Nepal Agricultural Research Council Vol.3 2017: 49-59